ESL TEACHERS AND STUDENTS PERCEPTIONS TOWARDS USAGE OF POWERPOINT AT UNIVERSITY LEVEL IN PUNJAB PAKISTAN - Asmara Batool; Dr. Perveen Akhter Farhat; Aleena Khan; Sumayya Kainat (International Journal of Contemporary Issues in Social Sciences, 2023)
Technological advancement with its extensive use in every field of life has also encouraged the instructors to apply innovative techniques in enhancing listening skill. PowerPoint is the latest technique which is gaining popularity. The current research intends to explore the perceptions of students and teachers about the usage of PowerPoint. The population of the study comprised of ESL students and teachers studying in the universities. For ethical consideration universities names were not mentioned. Using survey technique, from the entire population, fifty ESL students and fifty ESL teachers from these universities were randomly selected for sampling. The data were collected through a close ended, and demographical questionnaire. The questionnaire was containing on twelve close ended questions, six were asked from ESL teachers and six from ESL students. The questionnaire was sent to the participants by means of social media especially WhatsApp and Emails for data collection. The collected data were later analyzed comprehensively and presented in figures and graphs. ESL teachers and students showed that PowerPoint enhances learning motivation, vocabulary, listening skills and provides good content for better grammar usage, saves time etc. The results illustrated that the university students have shown positive inclination towards the use of power point for enhancing listening skill.